Motivasi dan Minat Berwirausaha Ditinjau dari Pengetahuan Kewirausahaan dan Persepsi Peluang Kerja Pada Mahasiswa STIE AMM Mataram - Hengki Samudra; Satriawan Satriawan; Topan Siswanto (Valid: Jurnal Ilmiah, 2020)
This study aims to determine the significant influence between entrepreneurship knowledge and Job Opportunities Perception on motivation and interest in student entrepreneurship. This study was designed with a quantitative research approach aimed at looking at the influence between variables in research. The sampling technique used is nonprobability sampling technique with a purposive sampling approach. With a total sample of 100 respondents. data collection tools using a questionnaire with a measurement of differential semantic scale. Data processing tools use structure equation modelling. Processing of research data begins with exogenous and endogenous confirmatory factor (CFA) analysis testing and results in the fulfillment of exogenous and endogenous CFA requirements. Where the significance requirements P ≤ 0.05 and the value of C. R ≥ 2, so that those who meet these requirements are entrepreneurial knowledge (KWN) influence on motivation where p = 0.001; and C.R = 3.208. So that the results of data processing show that entrepreneurial knowledge has a significant effect on motivation, perceptions of business opportunities have no significant effect on motivation, entrepreneurial knowledge has no significant effect on interests, Perception of business opportunities has no significant effect on interests, and motivation has no effect on interests